The Islamic Perspective on Economic Freedom: Freedom of Thought, Price Stability, and Market Dynamics Platform - vella, putri; ‘Alim, Sarirotul; Nur Aisyah, Binti; Nur Aisyah, Mashudi (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2026)
Economic freedom is one of the fundamental aspects of human life and is also regulated in Islamic teachings. Islam grants individuals the freedom to engage in business and innovation, yet this freedom is bound by Sharia principles that prohibit practices such as usury (riba), uncertainty (gharar), and monopoly. This study aims to analyze the Islamic perspective on economic freedom through a case study of the micro, small, and medium enterprise (MSME) Krupuk Rambak Lestari Eco in Tulungagung, focusing on intellectual rights, price stability, and the dynamics of digital platform markets. The research employs a descriptive qualitative method with data collected through interviews, observation, and documentation. The findings indicate that the MSME successfully implements Sharia-compliant economic freedom by developing business innovations, maintaining price stability to ensure fairness and affordability, and utilizing digital platforms to expand its market ethically. The study concludes that economic freedom in Islam can be practically applied in MSME management while upholding the values of justice, transparency, and Islamic business ethics.